Desain Organisasi dalam Pelaksanaan Program Pencegahan dan Pengendalian Penyakit Tidak Menular di Dinas Kesehatan Kota Samarinda - Harun; Paselle, Enos; Maulidah, Maulidah; Alamin, Fathul; Hendri; Ernita, Lina (PERSPEKTIF, 2024)
This study aims to identify Organizational Design in the Implementation of the Non-communicable Disease Prevention and Control Program in the Samarinda City Health Office. The problem focused on elements in Henry Mintzberg's organizational design: operating core, strategic apex, middle line, technostructure, and support staff. The data were collected from the results of in-depth interviews, observations, and document reviews supported by secondary data and analyzed qualitatively. Interviews were conducted with key informants, namely the Head of the Samarinda City Health Office; the main informant is the Head of Disease Prevention and Control; and supporting informants are Health Administrator of Non-communicable Disease Prevention and Control This study concluded that the implementation of the non-communicable disease prevention and control program at the Samarinda City Health Office followed the design of the machine organization, although there has been a simplification of bureaucracy, many and detailed standardizations and a strong chain of command cause the characteristics of centralization are still quite high. From the results of the study, it was also obtained that the existing organizational design was able to improve performance in the Implementation of the Non-communicable Disease Prevention and Control Program at the Samarinda City Health Office, the impact of which was seen from the increase in the achievement of Minimum Service Standards services for the Non-communicable Disease Prevention and Control program for the last 2 years.